Personal Narratives in Technology Design: The Value of Sharing Older Adults’ Stories in the Design of Social Robots - Ostrowski, Anastasia K.; Harrington, Christina N.; Breazeal, Cynthia; Park , Hae Won (Frontiers in Robotics and AI, 2021)
The storytelling lens in HCI has primarily focused on personas, design fiction, and other stories crafted by designers, yet informal personal narratives from everyday people have not been considered meaningful data, such as storytelling from older adults. Storytelling may provide a clear path to conceptualize how technologies such as social robots can support the lives of older or disabled individuals. To explore this, we engaged 28 older adults in a year-long co-design process, examining informal stories told by older adults as a means of generating and expressing technology ideas and needs. This paper presents an analysis of participants’ stories around their prior experience with technology, stories shaped by social context, and speculative scenarios for the future of social robots. From this analysis, we present suggestions for social robot design, considerations of older adults’ values around technology design, and promotion of participant stories as sources for design knowledge and shifting perspectives of older adults and technology.